Development and Assessment of a Teacher Education Course on Indigenous Perspectives: The Case of a Quebec University - Lavoie, Constance; Blanchet, Patricia-Anne; Edward, Kara; Robinson, Loretta; O'Bomsawin, Suzie; Moisan, Sabrina; Bernard, David; Joncas, Jo Anni (Journal of the Canadian Association for Curriculum Studies, 2024)
The 62nd Call to Action of the Truth and Reconciliation Commission of Canada (TRC, 2015) urges governments to "provide the necessary funding to post-secondary institutions to educate teachers on how to integrate Indigenous knowledge and teaching methods into classroom" (p. 256). While the province of Quebec is just beginning this process, several Canadian universities have already begun the process of indigenizing their teacher education programs. This article recounts the journey of including a course on Indigenous perspectives in the Faculty of Education at the University of Sherbrooke, Quebec. The rationale and results are organized around two questions: How can a course on Indigenous perspectives be developed for pre- service teacher education programs? How do teacher candidates who have taken this course feel about it? Methodologically, this study follows a collaborative action research process. Eleven individuals participated in the development of the course and twenty-five teacher candidates provided feedback. Preliminary findings reveal the importance of co-construction and co- development of such a course by and with Indigenous individuals and school organizations. It is apparent that teacher candidates, both Indigenous and non-Indigenous, finished this course satisfied and committed to including Indigenous perspectives in their classrooms.